The impact of visual search in Chinese children with developmental dyslexia on reading comprehension: the mediating role of word detection skill and reading fluency - Meng, Hu; Yao, Ru; Zhang, Pan; Wang, Jialei; Zhang, Yajing (Frontiers in Psychology, 2024)
Previous research has highlighted the influence of visual search on reading comprehension; however, the underlying mechanisms of this effect remain poorly understood, particularly in children with reading disabilities. This study investigates disparities in visual search, word detection skills, reading fluency, and reading comprehension between Chinese children with developmental dyslexia and their typically developing peers across different age groups. The sample comprised 191 students from grades 2, 4, and 6, including 92 children with dyslexia and 99 chronological age-matched typically developing children. Variance analysis revealed that children with developmental dyslexia performed significantly lower in visual search and reading comprehension tasks compared to their peers, with notable differences emerging primarily in the middle to higher grades. Additionally, these children exhibited weaker word detection skills and reading fluency, with disparities evident from the lower grades and persisting into the higher grades. Structural equation modeling indicated that visual search directly influences reading comprehension and indirectly affects it through mediating pathways involving word detection skills and reading fluency. These findings elucidate the complex interplay between visual processing and linguistic skills in reading development, particularly within the context of the Chinese language. They underscore the importance of tailored interventions to support children with dyslexia, emphasizing the need for strategies that address the unique challenges faced by these learners in Chinese reading environments.